Adsorption by powders and porous solids principles, methodology and applications - Rouquerol, Franðcoise (Amsterdam Boston Academic Press, 2014)
The declared objective of this book is to provide an introductory review of the various theoretical and practical aspects of adsorption by powders and porous solids with particular reference to materials of technological importance. The primary aim is to meet the needs of students and non-specialists who are new to surface science or who wish to use the advanced techniques now available for the determination of surface area, pore size and surface characterization. In addition, a critical account is given of recent work on the adsorptive properties of activated carbons, oxides, clays and zeolites. Key Features Provides a comprehensive treatment of adsorption at both the gas/solid interface and the liquid/solid interfaceIncludes chapters dealing with experimental methodology and the interpretation of adsorption data obtained with porous oxides, carbons and zeolitesTechniques capture the importance of heterogeneous catalysis, chemical engineering and the production of pigments, cements, agrochemicals, and pharmaceuticals.
Includes index.
Keywords: Adsorption; Porous materials; Powders; Electronic books